Shrimp Nugget Processing Training as an Innovation for SMEs in Tajungan Village, Kamal, Bangkalan: Array - Dina Ayu Setyobudi; Ulfatun Ni’mah; Nadhiya Aufa (Lembaga Citra Pustaka, 2022)
The village is one of the strategic areas that has a variety of natural potential it has. And has a role in supporting development. One of them can be observed from the implementation of Village-Owned Enterprises (BUMDES), which is an institution that is able to optimize various superior businesses owned by the village so that villages can become independent and efficient for the community. One of them is Tajungan village which is located in Kamal District, Bangkalan Regency, East Java. This area independently already has a business that is formed in a small business group that is developing in the seafood sector, especially food processing made from shrimp, such as shrimp crackers and shrimp sewel. There are still no people in the village of Tajungan who use marine catches to make shrimp nuggets. Here we held training on processing shrimp nuggets as an innovation of processed products from marine catches to increase MSMEs in Tajungan village, Kamal district, Bangkalan district, East Java.